Vehicle Routing Problem with Intermediate Facilities - Campos Ducasse, Pablo (2012)
In the search for efficiency as one of the main means to be an important player in the current globalized markets, a procedure is developed in this research trying to identify potential benefits of including intermediate facilities for the delivery stage of a distribution system. The specific purpose is to improve the efficiency of a vehicle which has to serve several clients in a region and for this a heuristic is developed. This procedure has as base a heuristic to solve the p-median problem and another one for the construction of routes. Then, a stage to improve the solution is added. This heuristic is used to evaluate different instances generated for the vehicle routing problem with intermediate facilities. From the results generated it may be seen that the density, the local distances, the radial distances, and other characteristics have a very important impact in the savings that can be obtained with the inclusion of intermediate facilities.